2000
DOI: 10.1007/s004170000166
|View full text |Cite
|
Sign up to set email alerts
|

Spatial localisation: does extraocular muscle proprioception play a role?

Abstract: Our ability to determine the position of targets in surrounding visual space (spatial localisation) is an important aspect of visual function and requires the integration of both visual (ie retinal) and non-visual (ie extraretinal) information. Afferent signals derived from extraocular muscle proprioceptors are though to contribute to this extraretinal information. However, this has proved to be a contentious issue. This article considers the role of extraocular muscle proprioception in spatial localisation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Although the timing of the updating effect may also be compatible with other sources of information, such as proprioception, saccade‐related information seems to be provided by a corollary discharge signal of the saccadic movement command. Although proprioception plays a role in providing spatial constancy, corollary discharge is much more important (Bridgeman, 1995; Weir, 2000). Post‐saccadic ERP components in earlier studies have also been attributed to incoming corollary discharge or efference copy information in the parietal cortex (Skrandies & Laschke, 1997; Anagnostou et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although the timing of the updating effect may also be compatible with other sources of information, such as proprioception, saccade‐related information seems to be provided by a corollary discharge signal of the saccadic movement command. Although proprioception plays a role in providing spatial constancy, corollary discharge is much more important (Bridgeman, 1995; Weir, 2000). Post‐saccadic ERP components in earlier studies have also been attributed to incoming corollary discharge or efference copy information in the parietal cortex (Skrandies & Laschke, 1997; Anagnostou et al.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to be brought about by a form of proprioceptive feedback from both the neck 4 and the extraocular muscles, 5 which relocates the efference copy map to match the amount of head and eye rotation with respect to the body. It is therefore not surprising that patients with neck pathology, 6 squint 5 and restricted eye movements 7 may have a sensation that the visual surroundings are not quite where they think they are, leading to a sense of imbalance and clumsiness. The symptoms are difficult to describe because these are subconscious automatic functions that are disordered.…”
Section: Moving the Visual Mapfneck And Extraocular Muscle Propriocepmentioning
confidence: 99%
“…Experiments in humans using vibration of muscles have shown that there is an influence from proprioceptors in the postural, neck and eye muscles on the perception of target localization in space (Roll et al. 1989; Weir 2000). The different movement and visual illusions induced by vibration of the lateral rectus muscle are shown in Fig.…”
Section: Sensory Function Of Eye Musclesmentioning
confidence: 99%